The Cauchy Problem for Quasilinear Systems of Functional Differential Equations - Grigorian, G. A. (Sarajevo Journal of Mathematics, 2024)
We use the contracting mapping principle to prove that under some mild restrictions, the Cauchy problem for quasilinear systems of functional differential equations with retarded arguments has a unique solution. As a consequence of this result, we obtain that the Cauchy problem for linear systems of functional differential equations with locally integrable coefﬁcients and with locally measurable retarded arguments has a unique solution. We show that similar results can be obtained for the Cauchy co problem of quasilinear systems of functional differential equations with advanced arguments.